Japanese Encephalitis Virus Exploits Dopamine D2 Receptor-phospholipase C to Target Dopaminergic Human Neuronal Cells - Simanjuntak, Yogy; Liang, Jian-Jong; Lee, Yi-Ling; Lin, Yi-Ling (Frontiers in Microbiology, 2017)
Despite the availability of vaccines for Japanese encephalitis virus (JEV), the re-emerging virus remains a clinically important pathogen that causes acute encephalitis and permanent neuropsychiatric sequels. JEV highly targets dopaminergic neuron-rich brain regions including the thalamus and midbrain. The molecular mechanism contributing to the high susceptibility of these particular brain regions remains largely unclear. This study addressed whether this tissue tropism of JEV is associated with signaling of dopaminergic neurons. Three pieces of evidence indicate that JEV exploits dopamine signaling to facilitate its infection: (1) JEV infection modulates dopamine level; (2) a selective dopamine D2 receptor (D2R) agonist enhances JEV infection; and (3) stimulation of D2R activates phospholipase C (PLC) to enhance the surface expression of JEV binding/entry molecules, integrin β3 and vimentin. Overall, JEV may exploit dopamine-mediated neuronal communication to increase the susceptibility of D2R-expressing cells to JEV infection. This study identifies a potential underlying mechanism of viral invasiveness in the dopaminergic brain regions and suggests antiviral strategies against viral infection by targeting D2R-PLC signaling.